Peran dan Tugas Wali Baptis di Paroki Hati Kudus Yesus Laham - Agustina Mayang; Wilfridus Samdirgawijaya (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2018)
This study used the qualitative approach. The variable in this study was the comprehension of the role and duty. The theory used to measure the Catholics comprehension was instrumental comprehension and relations comprehension according to Richard R. Skemp. The indicator of theory is he role and duty. The technique of data collection used in this study was observation and interview. The result of the study indicated that the Catholics’ comprehension of the parish of “Hati Kudus Yesus” Laham in accordance with the role and duty of the godparents was the instrumental comprehension, because the Catholics’ comprehension was only for one classification, that is, the role and duty of the godparents at the baptizing ceremony. The Catholics do not know the role and the duty of the godparents before and after the baptizing. Therefore, the Catholics comprehension can be categorized into the instrumental comprehension formally and ceremonially.